2011
DOI: 10.1038/onc.2010.616
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor regulates Mcl-1 expression through the MAPK-Elk-1 signalling pathway contributing to cell survival in breast cancer

Abstract: Myeloid cell leukaemia-1 (Mcl-1) is an anti-apoptotic member of the Bcl-2 family that is elevated in a variety of tumour types including breast cancer. In breast tumours, increased Mcl-1 expression correlates with high tumour grade and poor patient survival. We have previously demonstrated that Her-2 levels correspond to increased Mcl-1 expression in breast tumours. Epidermal growth factor (EGF) receptor signalling is frequently deregulated in breast cancer and leads to increased proliferation and survival. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 56 publications
8
100
1
Order By: Relevance
“…EGF has been shown to increase Mcl-1 and block hypoxia induced cell death. 6 We showed that EGF treatment of cells transfected with BNIP3 expression vector (BNIP3) reduced the ability of BNIP3 in induce cell death (Fig. 8B).…”
Section: Hypoxia Induced Cell Death Involves Bnip3 Expression and Is mentioning
confidence: 87%
See 3 more Smart Citations
“…EGF has been shown to increase Mcl-1 and block hypoxia induced cell death. 6 We showed that EGF treatment of cells transfected with BNIP3 expression vector (BNIP3) reduced the ability of BNIP3 in induce cell death (Fig. 8B).…”
Section: Hypoxia Induced Cell Death Involves Bnip3 Expression and Is mentioning
confidence: 87%
“…4 At the transcriptional level, Mcl-1 is regulated by several transcription factors, including members of the STAT family and Elk-1. 4,6 Mcl-1 is also regulated at the translational level by several mechanisms controlling both caspase and proteasomal degradation. 4 Posttranslational modifications, such as phosphorylation and ubiquitination also allow for tight regulation of Mcl-1 stability and degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In lung cancer, activation of STAT3 and NF-κB are frequently observed and their roles have been analyzed experimentally [12][13][14][15][16] . Moreover, STAT3 and ELK-1 are activated by EGFR (epidermal growth factor receptor) 13,14 .…”
mentioning
confidence: 99%